2010
DOI: 10.1073/pnas.0913449107
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synaptic connectivity and epilepsy in C1q knockout mice

Abstract: Excessive CNS synapses are eliminated during development to establish mature patterns of neuronal connectivity. A complement cascade protein, C1q, is involved in this process. Mice deficient in C1q fail to refine retinogeniculate connections resulting in excessive retinal innervation of lateral geniculate neurons. We hypothesized that C1q knockout (KO) mice would exhibit defects in neocortical synapse elimination resulting in enhanced excitatory synaptic connectivity and epileptiform activity. We recorded spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
259
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(269 citation statements)
references
References 32 publications
10
259
0
Order By: Relevance
“…It is known from post-natal studies that complement proteins mediate microglia-dependent pruning of synapses within neuronal circuits. As such, C1q-deficient mice display abnormal neocortical excitatory synaptic connectivity, as well as enhanced epileptiform activity (Chu et al, 2010). These evidences suggest a possible reactivation of developmental pathways also in adult CNS disorders (Stevens et al, 2007).…”
Section: Neuronal Functional Plasticitymentioning
confidence: 87%
“…It is known from post-natal studies that complement proteins mediate microglia-dependent pruning of synapses within neuronal circuits. As such, C1q-deficient mice display abnormal neocortical excitatory synaptic connectivity, as well as enhanced epileptiform activity (Chu et al, 2010). These evidences suggest a possible reactivation of developmental pathways also in adult CNS disorders (Stevens et al, 2007).…”
Section: Neuronal Functional Plasticitymentioning
confidence: 87%
“…Synaptic, neuronal and axonal pruning is an essential step during brain development, starting early after birth and completed around the time of sexual maturation [for review see: (Luo and O'Leary 2005)] and has been found in rats (Andersen and Teicher 2004) as well as in humans (Glantz et al 2007). Failure to prune excessive excitatory synapses during development has been linked to epileptogenesis in a C1q knockout mice model (Chu et al 2010), but it is unknown whether a pruning dysregulation plays a role in the tetanus toxin epilepsy model.…”
Section: Normal Brain Developmentmentioning
confidence: 99%
“…Recently, C1q was found to participate in synapses remodeling and in the clearance of damaged CNS neurons after neuronal injury and neurodegenerative disorders (36)(37)(38). Again, both C1q and C3 binding to damaged neurons is required for efficient silent phagocytosis of apoptotic cells (16).…”
Section: Discussionmentioning
confidence: 99%